Assessment of physiological properties and toxic heavy metal concentration of drinking water from the old faithful spring Fountain (Artesian Well) and commercial water refilling stations in Bauan, Batangas - Marquez, Danielle B.
Billions of people around the world still lack access to safe drinking water. In the Philippines, common drinking water sources include groundwater and water refilling stations (WRS). However, risks of contamination of these sources are still present and threaten public health and safety. In this study, drinking water from an artesian well (Location D) and three water refilling stations—Aquasilo WRS, Love WRS, and MielJosh Earth WRS (Locations A, B, and C, respectively) were evaluated in terms of their pH and Total Dissolved Solids (TDS) levels and toxic heavy metal (arsenic, cadmium, and lead) concentration. The pH values of water samples from all locations passed the Philippine National Standards for Drinking Water (PNSDW). In terms of the TDS levels, only the water samples from locations B and D passed the PNSDW. As for toxic heavy metals, the As, Cd, Pb contents of water samples from all locations were below detection limits, except those from location D with As levels beyond maximum allowable levels (MAL). Statistical analyses carried out through Kruskal-Wallis test followed by Mann-Whitney test disclosed differences in the pH and TDS levels among water samples across all sampling locations, with locations B and D having the lowest and highest values, respectively. The Spearman correlation test showed a strong positive relationship between the pH and TDS values, and between pH and As, indicating the ability of pH to influence behaviors of other quality parameters that affect water quality. Despite the satisfactory results of some parameters based on the PNSDW, the elevated levels of TDS and As detected in several samples suggest that the drinking water from these sources may be unfit for human consumption. Constant monitoring of drinking water quality and the use of efficient water treatment systems are crucial in ensuring a more sustainable living environment for communities in terms of nutrition, health, and overall well-being.